PEER EVALUATION IN WRITING: HOW TO IMPLEMENT EFFICIENTLY - Tuzcu Eken, Derya (International Online Journal of Education and Teaching, 2021)
The aim of this paper is to investigate the most efficient ways to apply peer evaluation in writing courses, and lack of studies on the views of students’ experienced difficulties while responding to their peers’ papers is the starting point of this paper. For this cause, case study method was implemented including an interview conducted with prep-class students (N=37) who attended a writing course for two semesters and a document analysis of related papers written over the past five years that specifically focuses on the ways to develop peer-evaluation skills of students. For the interview, content analysis was applied to define the themes. The relevant papers, on the other hand, were analysed through document analysis. As a result of the study, it was found that students, especially the ones that are not so good at writing in English, experience difficulty in applying peer evaluation and prefer teacher evaluation to peer evaluation. Moreover, most of the students are not so much aware of the dual benefits of peer evaluation. Consequently, students need effective peer evaluation activities to enhance their skills beforehand. The suggestions collected thanks to the documents analysed to this end is expected to be helpful.